Nanofibre-assisted alignment of carbon nanotubes in macroscopic polymer matrix via a scaffold-based method (eXPRESS Polymer Letters, 2010)
A facile way for alignment of carbon nanotubes in macroscopic polymer matrix was developed by combining electrospinning and in-situ polymerization. The approach is based on the formation of nanofibre scaffolds with wellaligned arrays, which is filled with carbon nanotubes (CNTs). CNTs will be well aligned in macroscopic polymer matrix when the aligned nanofibre scaffold containing CNTs has been incorporated into the poly(methyl methacrylate) (PMMA) matrix by in-situ polymerization. We demonstrate that this scaffold approach is broadly applicable and allows for the fabrication of nanocomposites with accurately aligned nanofillers. The results presented in this report show that the approach is ideal by using polyacrylonitrile (PAN) nanofibres as a scaffold of multiwalled carbon nanotubes (MWNTs), and PMMA as the macroscopic polymer matrix. The tensile strength (7.2 wt% MWNTs/PAN nanofibres loadings) reaches 48.61 MPa, 87% higher than that pure PMMA, and the tensile modulus is increased by 175%.